Interactive Visualization of BB84 Protocol for Teaching Quantum Cryptography - Santos, Walter H. A.; Menezes, Kauã O. S.; Santos, Lucas W.; Morais, Marcos V. S.; A. Neto, Antônio J. (Anais Estendidos do Simpósio Brasileiro de Cibersegurança (SBSeg), 2025)
This article does not have an abstract.